2020
DOI: 10.1016/j.jcp.2020.109695
|View full text |Cite
|
Sign up to set email alerts
|

Unstructured un-split geometrical Volume-of-Fluid methods – A review

Abstract: Please refer to the journal version when citing this work. Geometrical Volume-of-Fluid (VoF) methods mainly support structured meshes, and only a small number of contributions in the scientific literature report results with unstructured meshes and three spatial dimensions. Unstructured meshes are traditionally used for handling geometrically complex solution domains that are prevalent when simulating problems of industrial relevance. However, three-dimensional geometrical operations are significantly more com… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 68 publications
(29 citation statements)
references
References 78 publications
(313 reference statements)
0
29
0
Order By: Relevance
“…It uses the projection method to compute the velocity and pressure and the geometric volume-of-fluid method for the evolution of the interface between two immiscible fluids (Tryggvason, Scardovelli & Zaleski 2011). The Piecewise Linear Interface Calculation geometric interface and flux reconstruction ensures a sharp representation of the interface (Scardovelli & Zaleski 1999; Marić, Kothe & Bothe 2020) and is combined with an accurate height-function curvature calculation and a well-balanced, continuum surface tension model (Brackbill, Kothe & Zemach 1992; Popinet 2018).…”
Section: Numerical Frameworkmentioning
confidence: 99%
“…It uses the projection method to compute the velocity and pressure and the geometric volume-of-fluid method for the evolution of the interface between two immiscible fluids (Tryggvason, Scardovelli & Zaleski 2011). The Piecewise Linear Interface Calculation geometric interface and flux reconstruction ensures a sharp representation of the interface (Scardovelli & Zaleski 1999; Marić, Kothe & Bothe 2020) and is combined with an accurate height-function curvature calculation and a well-balanced, continuum surface tension model (Brackbill, Kothe & Zemach 1992; Popinet 2018).…”
Section: Numerical Frameworkmentioning
confidence: 99%
“…Realistic industrial injector geometries for atomization simulations are very complex, including sharp edges and narrow corners, which hinders the meshing task with cartesian grids: the use of unstructured meshes is thus well suited for this type of simulations [1]. Although the literature remains limited about unstructured atomization computations, previous studies on static meshes can be found, such as [2,3,4,5,6,7,8,9] for Volume Of Fluid (VOF) interface capturing techniques [10], or [11,12,13,14,15] for Level Set methods (LS) [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…The research on the geometric VOF methods has been a very active field in recent years, which is mainly focused on the interface reconstruction algorithms (e.g., References 18 and 19), interface propagation and advection schemes, 20,21 and especially implementation on unstructured grids for complex geometries (e.g., References 22‐25). The development of the geometric VOF method has been reviewed in the most recent study, 26 and interested readers are referred to the above papers and references therein.…”
Section: Introductionmentioning
confidence: 99%